Effect of Sn Doping on the Thermoelectric Properties of n-type Bi-2(Te,Se)(3) Alloys - Lee, Jae-Uk; Lee, Deuk-Hee; Kwon, Beomjin; Hyun, Dow-Bin; Nahm, Sahn; Baek, Seung-Hyub; Kim, Jin-Sang (SPRINGER, 2015)
In the present work, 0.01-0.05wt.% Sn-doped Bi-2(Te0.9Se0.1)(3) alloys were prepared by mechanical deformation followed by hot pressing, and their thermoelectric properties were studied. We observed that the Sn element is a very effective dopant as an acceptor to control the carrier concentration in the n-type Bi-2(Te0.9Se0.1)(3) alloys to optimize their thermoelectric property. The n-type carrier concentration can be controlled from 4.2 x 10(19)/cm(3) to 2.4 x 10(19)/cm(3) by 0.05wt.% Sn-doping. While the Seebeck coefficient and the electrical resistivity are both increased with doping, the power factor remains the same. Therefore, we found that the thermoelectric figure-of-merit becomes maximized at 0.75 when the thermal conductivity has a minimum value for the 0.03wt.% Sn-doped sample.
Keywords: PERFORMANCE; TELLURIDE; CRYSTALS; HEAT